ANALYSIS OF HEAT TRANSFER RATES DURING FLOW IN SMOOTH TURBULIZER TUBES (American Journal of Technology and Applied Sciences, 2023)
In this article, the increase of heat transfer in convective heat exchange during fluid flow in the channels of shell-and-tube heat exchangers used in industrial enterprises is studied. Based on the analysis of existing problems, it was determined to accelerate the process of heat transfer during the movement of the heat carrier flow in smooth and convex printed channels.